The Effects of Mental Health Literacy Programme (The CARE) for Secondary School Teachers - Supreeyaporn, Nanthaka; Sakulsriprasert, Chaiyun (Journal of Education Studies, Chulalongkorn University, 2024)
Teachers play a crucial role in providing primary mental health support to students. However, previous studies showed that teachers’ mental health literacy is still limited. Thus, the aim of this study was to examine the effects of mental health literacy programme (The CARE) for secondary school teachers. This study used a quasi-experimental research design (pretest-posttest with control group). The research involved 48 class teachers and guidance teachers from secondary schools in Chiang Mai province, selected through simple randomized sampling. The sample was divided into experimental and control groups, each consisting of 24 participants using simple random sampling. The research instruments comprised 1) a demographic questionnaire 2) a mental health literacy test for teachers, and 3) a questionnaire on perceived self-efficacy regarding mental health for teacher. Data were analysed using mean, standard deviation, chi-square (χ2), t-test, and repeated measures MANOVA. The results demonstrated that after participating in the programme, the experimental group had significantly higher mental health literacy scores (M = 15.83, SD = 1.60) and perceived self-efficacy score (M = 64.04, SD = 4.61) than the baseline at the .016 level of significance. Additionally, analysis of the interaction between the experimental and control groups and measurement time revealed a significant effect on both mental health literacy scores (F(1, 46)= 24.69, p = .000, η2 = .349) and perceived self-efficacy scores (F (1, 46) = 76.77, p = .000, η2 = .625). In conclusion, The CARE programme significantly enhances mental health literacy and strengthens perceived self-efficacy among secondary school teachers, equipping them to provide effective initial support to students with mental health needs in schools.